2013
DOI: 10.1021/ja407014w
|View full text |Cite
|
Sign up to set email alerts
|

Volatile and Thermally Stable Mid to Late Transition Metal Complexes Containing α-Imino Alkoxide Ligands, a New Strongly Reducing Coreagent, and Thermal Atomic Layer Deposition of Ni, Co, Fe, and Cr Metal Films

Abstract: Treatment of MCl2 (M = Cu, Ni, Co, Fe, Mn, Cr) with 2 equiv of α-imino alkoxide salts K(RR'COCNtBu) (R = Me, tBu; R' = iPr, tBu) afforded M(RR'COCNtBu)2 or [Mn(RR'COCNtBu)2]2 in 9-75% yields. These complexes combine volatility and high thermal stability and have useful atomic layer deposition (ALD) precursor properties. Solution reactions between Ni, Co, and Mn complexes showed that BH3(NHMe2) can reduce all to metal powders. ALD growth of Ni, Co, Fe, and Cr films is demonstrated. Mn film growth may be possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 32 publications
2
59
0
Order By: Relevance
“…The growth rate, ca. 0.09 Å/cycle, is similar to the values observed for the separate Cu (0.12 Å/cycle) and Mn (0.08 Å/cycle) processes (30,31). The compositions of the films are close to the idealized 70% Cu and 30% Mn on Si/SiO2, Co, Ru, and thermal SiO2 surfaces, but are Mn-rich on H-terminated Si.…”
Section: Ald Growth Of Cu/mn Alloy Filmssupporting
confidence: 78%
See 3 more Smart Citations
“…The growth rate, ca. 0.09 Å/cycle, is similar to the values observed for the separate Cu (0.12 Å/cycle) and Mn (0.08 Å/cycle) processes (30,31). The compositions of the films are close to the idealized 70% Cu and 30% Mn on Si/SiO2, Co, Ru, and thermal SiO2 surfaces, but are Mn-rich on H-terminated Si.…”
Section: Ald Growth Of Cu/mn Alloy Filmssupporting
confidence: 78%
“…Despite extensive efforts, we have been unable to prepare Cu precursors that have improved properties compared to Cu(dmap)2 (28,30). Accordingly, this Cu precursor was chosen for the present study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indirect methods like reduction of CuO by isoproponal 10 , Cu 2 O by formic acid over ruthenium 11 and Cu 3 N by H 2 12 have also been tried. Kalutarage et al 13 have reported the use of BH 3 (NHMe 2 )…”
Section: Introductionmentioning
confidence: 99%